FACTORS INFLUENCING THE INCIDENCE OF ANEMIA IN THIRD TRIMESTER PREGNANT WOMEN - Soya Nita, Elin; Pety Merita Sari; Candra Dewinataningtyas; Lisa Mayaningtyas (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Anemia during pregnancy remains a critical contributor to maternal and neonatal morbidity and mortality. Pregnant women affected by anemia are at an elevated risk of experiencing postpartum hemorrhage, a condition that can be life-threatening. The primary cause of anemia in pregnancy is iron deficiency. Preventive strategies can be significantly improved through educational interventions that enhance maternal knowledge and promote positive attitudes toward the importance of adequate nutritional intake during pregnancy. Method: This research utilized a quantitative analytic design with a cross-sectional approach. The study examined age, parity, and adherence to iron supplement consumption as independent variables, while the dependent variable was the occurrence of anemia in the third trimester of pregnancy. A total sampling technique was employed, Primary data were collected through questionnaires, maternal and child health (KIA) records, and laboratory test results. The data collected were analyzed using the Chi-square statistical test. Result: Among the participants, 53.3% of pregnant women aged 20–35 years were found to be anemic (n = 16). However, Chi-square analysis indicated no statistically significant association between age and anemia status (p = 0.645). Similarly, analysis of parity revealed a p-value of 0.214, suggesting no significant correlation. In contrast, compliance with iron tablet intake showed a statistically significant relationship with anemia incidence; 60% of non-compliant women (n = 18) were anemic, and the Chi-square test produced a p-value of 0.001, indicating a significant association (p < 0.05). Conclusion: The findings suggest that there is no significant relationship between age or parity and the incidence of anemia in third-trimester pregnant women. However, adherence to iron supplementation is significantly associated with anemia status, highlighting the importance of compliance in preventing anemia during pregnancy.